Zimbabwe Will Never be a Colony Again! : Sanctions and Anti-Imperialist Struggles in Zimbabwe - Mararike, Munoda (Book collections on Project MUSE., 2019)
This is a thought-provoking original book, based on a wealth of empirical case studies of how Zimbabwe experienced illegal economic sanctions. It is a study of how the humanly constructed obstructions -- from external remittances/finance flows into the country to finance embargos or total financial blockages -- are deliberately created by so-called 'powerful' governments to deal with an 'errand' country. The infamous Zimbabwe Democracy Economic Recovery Act of 2001 (ZDERA) is part of a raft of punitive measures and discourses that the USA, UK and Europe used to make the economy, in the words of US's Chester Crooker "scream". It is the same 'powerful' countries who allow their Multinational Corporations to loot while they impose sanctions against African governments and their peoples to make them scream. The book is an insightful contribution on Africa's contemporary post-colonial liberation politics of development economics. It focuses on Zimbabwe as a synthesis of microcosmic study that provides accessible in-depth analysis of key aspects of sanctions as a weapon of control wielded by the so-called 'powerful' governments of the Global North. Zimbabwe was clobbered with post-independence economic sanctions after its land reform programme, which benefitted its mostly colonially dispossessed African citizens. The land reform was intended as a reversal of colonial injustice and a counter restitutive measure against imperialism. The book invites the reader to see power differently: as compassion and the capacity to right past wrongs by protecting all and sundry from inequality and poverty. Sanctions, even when called targeted, are non-discriminatory as they affect ordinary citizens with the same ferocity and savagery as against intended target, albeit often missing the target. Sanctions are lethal. Sanctions are a graveyard for the poor, weak and vulnerable. This is an idea of power that the Global North failed to grasp when they decided to punish the Mugabe government for daring to contemplate justice and restitution.